Magnitude and predictors of common mental disorder among people with HIV/AIDS in Ethiopia: a systematic review and meta-analysis - Zelalem Belayneh; Birhanie Mekuriaw; Tsegaye Mehare; Saide Shumy; Mekonnen Tsehay (BMC, 2020)
Abstract Background Common mental disorders are frequent psychiatric comorbid conditions among people with HIV/AIDS. The presence of such psychiatric disorders negatively affects the treatment adherence, viral load suppression, quality of life, treatment outcomes and functionality of people with HIV/AIDS. However, available studies in Ethiopia have a great variation and inconsistency of reported results have been observed regarding the magnitude and associated factors of common mental disorder. Thus, conducting a systematic review and meta-analysis of existing literatures can have a paramount importance to show its summarized figure. Methods Literatures search was performed using databases (PubMed/Medline, Science Direct and PsycINFO. Grey literatures were also searched from Google and Google Scholar. Data were extracted from primary studies using a data extraction format prepared in Microsoft Excel and exported to STATA-version 14 statistical software for analysis. The I2 test was used to assess the heterogeneity of primary articles. The result of the test showed that there was heterogeneity between primary studies. This leads us to execute a random effect meta-analysis to estimate the pooled prevalence of common mental disorder with corresponding 95% confidence interval. Results A total of 13 primary studies comply with the inclusion criteria were included in this systematic review. The pooled prevalence of common mental disorder was found to be 28.83% (95% CI: 17.93, 39.73) among people with HIV/AIDS in Ethiopia. The highest prevalence of common mental disorder (35.20%) was observed among studies in which Kessler-10 was used as a screening tool. Single marital status (OR = 1.83; 95%CI: 1.03, 3.27), HIV/AIDS-related stigma (OR = 2.21; 95%CI: 1.68, 2.90) and current job unavailability (OR = 1.38; 95%CI: 1.01, 1.88) had statistically significant association with common mental disorder. Conclusion The result of this review showed that nearly one among three individuals with HIV/AIDS is suffering from common mental disorder in Ethiopia. This calls a need to integrate the mental health and psycho-social support into the HIV/AIDS care. Trial registration PROSPERO- CRD42019132402 . Registered on 05/08/2019.